2021
DOI: 10.1155/2021/9834770
|View full text |Cite
|
Sign up to set email alerts
|

Antiseismic Method of Prestressed Fabricated Building Structure under Intelligent Big Data

Abstract: Compared with traditional buildings, prefabricated buildings have the advantages of simple construction technology, low construction requirements, and shorter construction time, which can generate more economic benefits for the construction industry. In order to study the seismic capacity of prestressed fabricated building structures under intelligent big data, this article takes fabricated frame structures as the research object and the reinforced walls at the nodes as the starting point to study the damage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The study indicated that the prestressed assembled structure with axial compression ratio of 0.3 and prestress less than 0.5 has the best seismic performance, which is in line with the seismic design code. At the same time, the system also showed good self-healing properties and better seismic response to different seismic waves [8]. Ding et al developed a graduated intelligent manufacturing system in order to achieve stable, resilient, and applicable assembly production, real-time visibility and traceability of prefabricated production through IoT, and improved the performance level of scheduling and executing decisions under large fluctuations in runtime based on a multi-stage adaptive decision-making mechanism.…”
Section: Related Workmentioning
confidence: 99%
“…The study indicated that the prestressed assembled structure with axial compression ratio of 0.3 and prestress less than 0.5 has the best seismic performance, which is in line with the seismic design code. At the same time, the system also showed good self-healing properties and better seismic response to different seismic waves [8]. Ding et al developed a graduated intelligent manufacturing system in order to achieve stable, resilient, and applicable assembly production, real-time visibility and traceability of prefabricated production through IoT, and improved the performance level of scheduling and executing decisions under large fluctuations in runtime based on a multi-stage adaptive decision-making mechanism.…”
Section: Related Workmentioning
confidence: 99%